Kajian Pembelajaran Organisasi Dalam Rangka Pengembangan Sistem Informasi Manajemen Untuk Peningkatan Pelayanan Pelanggan di Perguruan Tinggi - Adhi Susano (LPPM, 2010)
In business development, especially in education lately has develop very rapidly. Competition was very tight for achieving the best. By which UNINDRA (especially FTMIPA) has to have long term organization purposes to get advanced superior competition, that is by having ability to learn more fast compare to its competitors, the faster organization can learn about new knowledge, then organization has one step faster compare to its competitors. FTMIPA is an organization in process of learning to aim at learning organization, by which an organization simply said as learning organization if the learning process happen and done by all organization element, which impact on behaviour of it members. This research draws learning process in five learning discipline according to Senge, which is personal mastery, mentals models, shared vision team learning and system thinking, by referring to Senge concept about learning organization, it is interesting to search how far the five learning discipline implicate on communication inside organization together with growing motivation to learn from organization member, and how far the learning process implicate in level of students satisfaction. In this research also used CDC EZTEXT program as tools in resulting conclusion from data gathered. Keywords : Learning Organization, Management Information System, Customer Service, Customer Satisfaction.